Antigenic characterization of 52–55 kDa protein isolated from Trypanosoma evansi and its application in detection of equine trypanosomosis. (October 2017) - Yadav, S.C.; Kumar, Ritesh; Kumar, Jaideep; Singh, Meetali; Bera, B.C.; Kumar, Rajender; Tatu, U.; Tehri, Kanika
Abstract: Trypanosoma evansi is a haemo-protozoan parasite responsible for the disease surra, an economically important disease of wide range of domestic and wild animals. The present diagnostic methods using soluble antigens have inherent problems like lack of standardized and reproducible antigens, as well as ethical issues. This entails further efforts for search of defined antigenic molecules with satisfying sensitivity and specificity for sero-epidemiology of trypanosomosis. In present investigation, we have identified and purified 52–55 kDa immuno-dominant protein cluster in molecular mass ranges by preparatory SDS-PAGE methods from T. evansi proteome. The purified protein was further characterized by hyper immune serum raised in rabbits and also further evaluated for its immunodiagnostic potential using experimentally infected horse serum samples by different immunological tests. The immunoblot, ELISA and dot blot assay using purified cluster in infected pooled serum samples showed detection of infection early as 10th days post infection till termination of experiment. The observations revealed that purified cluster is expressed not only at early stage but also persisted and detected throughout course of infection. Further, whole cell lysate antigen separated out and detected 141 spots by 2-D gel electrophoresis. The isoelectric focussing (PI) of 52–55 kDa was determined in pH range between 6.9 and 7.5 along with two other cluster of proteins recognised by immune sera of ponies infected with T. evansi . MS/MS analysis of the purified protein cluster identified five proteins i.e. pyruvate kinase 1, beta tubulin, paraflagellar rod protein, alanine aminotransferase and variable surface glycoprotein showing homology to protein present in Trypanosome database. These identified proteins may be useful for development of vaccines and diagnostic targets against animal trypanosomosis. Highlights: Polypeptide cluster (52–55 kDa) was purified from Trypanosoma evansi whole cell proteome. This native protein has shown immuno-diagnostic potential in ponies by immunological tests. LC-MS/MS analysis of tryptic digest of the purified protein identified five proteins. These proteins may be used as valuable, diagnostic/vaccine targets for T. evansi infection.